2017
DOI: 10.1111/1755-0998.12679
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA analysis identifies marine mollusc shells as new metagenomic archives of the past

Abstract: Marine mollusc shells enclose a wealth of information on coastal organisms and their environment. Their life history traits as well as (palaeo-) environmental conditions, including temperature, food availability, salinity and pollution, can be traced through the analysis of their shell (micro-) structure and biogeochemical composition. Adding to this list, the DNA entrapped in shell carbonate biominerals potentially offers a novel and complementary proxy both for reconstructing palaeoenvironments and tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 110 publications
4
86
2
Order By: Relevance
“…Despite recent advances in ancient genomics and the ecological relevance of mollusks, no mollusk genomic time transect has ever been produced. The potential of applying HTS to ancient marine mollusk shells has, however, been assessed for the first time in a recent study that revealed their metagenomic content (Der Sarkissian et al, 2017). This study identified species with aragonitic shell microstructures, such as Mytilus mussels, Haliotis abalones, Arctica islandica quahogs, and Venerupis/Ruditapes clams, as good candidates for mollusk DNA content and/or preservation, with the longest DNA survival observed for a Mytilus specimen dated to ∼7,000 years Before Present (year BP;Der Sarkissian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in ancient genomics and the ecological relevance of mollusks, no mollusk genomic time transect has ever been produced. The potential of applying HTS to ancient marine mollusk shells has, however, been assessed for the first time in a recent study that revealed their metagenomic content (Der Sarkissian et al, 2017). This study identified species with aragonitic shell microstructures, such as Mytilus mussels, Haliotis abalones, Arctica islandica quahogs, and Venerupis/Ruditapes clams, as good candidates for mollusk DNA content and/or preservation, with the longest DNA survival observed for a Mytilus specimen dated to ∼7,000 years Before Present (year BP;Der Sarkissian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, museum specimens can be considered genomic resources (McCormack, Rodríguez-Gómez, Tsai, & Faircloth, 2017) and can be used for diverse types of studies. Examples of such studies are fine-scale population genomics and genotyping (Bi et al, 2013;Lim & Braun, 2016), genome sequencing (Staats et al, 2013), metagenomics (Der Sarkissian et al, 2017), epigenomics (Rubi, Knowles, & Dantzer, 2019), barcoding (Miller, Beentjes, van Helsdingen, & IJland, 2013); Prosser, deWaard, Miller, & Hebert, 2016), species delimitation (Hedin, Derkarabetian, Blair, & Paquin, 2018;Kehlmaier et al, 2019), and phylogenomics (Blaimer, Lloyd, Guillory, & Brady, 2016;Hedin, Derkarabetian, Ramírez, Vink, & Bond, 2018;Ruane & Austin, 2017;Sproul & Maddison, 2017;Starrett et al, 2017;Wood, González, Lloyd, Coddington, & Scharff, 2018), including phylogenomic studies that incorporate genetic data from rare, endangered and/or extinct taxa held in historical collections (Hedin, Derkarabetian, Blair, et al, 2018;Oliveros et al, 2019;Tsai et al, 2019). This was not the case just a few years ago, when historical museum samples were not routinely used for molecular work.…”
mentioning
confidence: 99%
“…Ancient environmental DNA is becoming increasingly used as a tool to understand past environments (Der Sarkissian et al, ; Pedersen et al, ), address important ecological and evolutionary questions over expanded temporal frames (Hofreiter et al, ; Orlando et al, ; Rawlence et al, ), estimate biodiversity (Willerslev et al, ) and detect cryptic or rare (Malaspinas et al, ; Orlando et al, ) and invasive species from sediment or water samples (Martin et al, ; Pedersen et al, ). Our results indicate that incorporating ancient DNA in the form of palaeoecological environmental DNA (aeDNA) data in traditional palaeoecological studies of coral reefs represents a significant development for understanding the historical ecological role of coral reef organisms that do not leave a fossil record.…”
Section: Discussionmentioning
confidence: 99%